Propagation of noise generated by a tram moving with uniform motion - BEREZOWSKA-APOLINARSKA, Krystyna (Archives of Acoustics, 1986)
The registration of level changes of sound generated by a single source (e.g. a rail-vehicle — tram) allows the determination of the resultant level of noise emitted by sets of mobile sources (e.g. rail-vehicle lines). Research was aimed at the determination of the relationship between parameters a and L_AX, which characterize the noise of a single source, and the distance from the observation point, d. Investigations were conducted in a not built-over, flat and covered by grass area, for various types of trams and several speeds.